Kepailitan Sebagai Alasan Pemberhentian Notaris Di Indonesia - Weda, I Nyoman Ganang Bayu; Resen, Made Gde Subha Karma (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 01 (2022), 2022)
The objective on this paper is to finding legal position of a notary who is declared bankrupt and the bankruptcy which is used about a reason that dishonorable dismissal of  notary from his position. In this researched, authors used a normative methods research. The study indicated that : 1. Having a position as a legal subject of a person, not as a legal entity, this is because what is stated as a legal subject is a legal entity and a person, while notaries are not legal entities, but only represent legal subjects of people 2. Referring to the principle of lex specialist derograt legi generalis, Bankruptcy in the Notary law and bankruptcy law respects the position of the bankrupt party, However bankruptcy in this UUJN can involve the position as a Notary if this bankruptcy is the result of a mistake made by someone in his position as a Notary.